The Phoenix model of disengagement and deradicalisation from terrorism and violent extremism - Silke, Andrew; Morrison, John; Maiberg, Heidi; Slay, Chloe; Stewart, Rebecca (De Gruyter, 2021)
Improving our understanding of how disengagement and deradicalisation from terrorism and violent extremism occurs has critical real-world implications. A systematic review of the recent literature in this area was conducted in order to develop a more refined and empirically-derived model of the processes involved. After screening more than 83,000 documents, we found 29 research reports which met the minimum quality thresholds. Thematic analysis identified key factors associated with disengagement and deradicalisation processes. Assessing the interactions of these factors produced the Phoenix Model of Disengagement and Deradicalisation which is described in this paper. Also examined are some of the potential policy and practice implications of the Phoenix Model, as are avenues for future research in this area.
Keywords: disengagement; deradicalisation; terrorism; violent extremism; political violence; phoenix model